2018
DOI: 10.1007/s00464-018-6089-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative combination of progressive pneumoperitoneum and botulinum toxin type A in patients with loss of domain hernia

Abstract: Using a CT volumetric protocol, combination of PPP and BT decreases the VIH/VAC ratio and hernia defect diameters, which constitutes a key factor in the treatment of LODH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 27 publications
0
55
0
8
Order By: Relevance
“…Our search yielded 47 articles, and 10 met our inclusion criteria for review [14,[16][17][18][19][20][21][22][23][24] . Two independent reviewers assessed the articles for inclusion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our search yielded 47 articles, and 10 met our inclusion criteria for review [14,[16][17][18][19][20][21][22][23][24] . Two independent reviewers assessed the articles for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…Injection sites ranged from 3-5 points on each side of the abdomen. Six studies injected BTA into all three muscle layers of the abdominal wall for each injection site [17][18][19][20][21]23] . Elstner et al [22] compared injection at all three of the external oblique (EO), internal oblique (IO), and transversus abdominis (TA) muscles, to injection at only the EO and IO.…”
Section: Botulinum Toxin a Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…The term ‘loss of domain’ (LOD) is used widely amongst surgeons to describe the relationship between ventral hernia (VH) volume and residual abdominopelvic cavity volume; hernias with significant LOD are difficult to repair and are more likely to recur . However, the term appears loosely defined: A recent systematic review demonstrated considerable confusion, finding multiple different written and volumetric definitions .…”
Section: Question 1: Schematic Diagram Annotationmentioning
confidence: 99%
“…primary fascia closure) becomes clinically significant. It is claimed that LOD is a useful prognostic factor for recurrence but, for this to be true, a threshold value should be identified and recognized.…”
Section: Question 1: Schematic Diagram Annotationmentioning
confidence: 99%